2022
DOI: 10.3389/fmed.2022.830515
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Deep Learning Techniques for Tuberculosis Detection From Chest Radiograph

Abstract: The high mortality rate in Tuberculosis (TB) burden regions has increased significantly in the last decades. Despite the possibility of treatment for TB, high burden regions still suffer inadequate screening tools, which result in diagnostic delay and misdiagnosis. These challenges have led to the development of Computer-Aided Diagnostic (CAD) system to detect TB automatically. There are several ways of screening for TB, but Chest X-Ray (CXR) is more prominent and recommended due to its high sensitivity in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…EfficientNetV2 [ 30 ] was adopted in our study, which had shown superior efficiency in previous studies [ 39 , 40 ]. Our CAD algorithm’s performance was further augmented through an ensemble [ 41 ], which was expected to prevent the algorithm from overfitting on a small dataset, thus improving its potential for external generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…EfficientNetV2 [ 30 ] was adopted in our study, which had shown superior efficiency in previous studies [ 39 , 40 ]. Our CAD algorithm’s performance was further augmented through an ensemble [ 41 ], which was expected to prevent the algorithm from overfitting on a small dataset, thus improving its potential for external generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…The TBNet framework supports a contextaware graph network to diagnose TB. 8,9,[25][26][27] Thus, these research works demonstrated the potential of various image processing techniques and machine learning algorithms used in pulmonary image analysis, providing insights for the development of more accurate and efficient diagnostic tools for lung diseases.…”
Section: Review On Fuzzy Based Machine Learning Techniquesmentioning
confidence: 94%
“…It employed deep learning techniques to detect TB from chest radiograph. The TBNet framework supports a context‐aware graph network to diagnose TB 8,9,25–27 …”
Section: Related Workmentioning
confidence: 99%
“…However, these reviews are very specific and focus on single diseases like pneumonia (Khan et al. 2021 ), lung cancer (Pratim and Nachamai 2022 ), tuberculosis (Oloko-Oba and Viriri 2022 ), pulmonary nodule detection (Li et al. 2022 ), and COVID19 detection (Chen et al.…”
Section: Introductionmentioning
confidence: 99%